European post-socialist cities and their near hinterland in intra-urban geography literature - KubešCDFMR Jan (Bulletin of Geography. Socio-Economic Series)
Over 180 articles concerning urban geography aspects of European post-socialist cities and their near hinterland, published between 1990-2012 in international journals, were selected for the analysis in this paper. Statistics of articles by journals, analysed cities (and their countries) and authors proves the preponderance of research on post-socialist Central European capitals, especially Berlin, Prague and Budapest, followed by Leipzig and Łodź, as well as Moscow and Tallinn. It also proves that the number of domestic authors and those who moved from post-socialist Europe to Western universities gradually increased, while the number of authors from the West decreased. The analysis of representations of article topics, their explanations and justifications were carried out in the second part of the paper. The most frequent article topics include ‘social spatial structure of the city and its transformation’, followed by ‘urban planning and management in the city’ and ’suburbanisation and urban sprawl in the near hinterland of the city’. A smaller number of articles refers to ‘physical spatial structure of the city and its transformation’, ‘housing structure in urban neighbourhoods in connection with changes in housing policy and market’ and ‘functional spatial structure of the city and its transformation’. Indexes of the articles are part of this paper